Desain dan Perhitungan Biaya Pembangunan Drainase Jalan Sapta Marga Kabupaten Merangin - Purnama, Gegen; Radinal, Radinal; Wijaya, Sucitra (CV Edujavare Publishing, 2024)
In the current era of globalization, an area certainly requires adequate urban facilities and infrastructure to support the needs of the population. Based on field observations, Jalan Sapta Marga, Pematang Kandis Village, Bangko District, Merangin Regency does not have adequate drainage channels. The purpose of this study was to determine the design of the channel, the volume of construction, and the budget plan needed for drainage in the Sapta Marga Environment, Pematang Kandis Village, Bangko District, Merangin Regency. This research method uses an applied research approach. The research process begins with a study of the problem to be studied, the next process is to search for a project that will be used as a medium for applying the problem. The data required is obtained directly from project documents. The results of this study indicate that the results of the secondary channel cross-section design are in the form of an open channel and a trapezoidal cross-section. Based on the results of the analysis and calculation of the RAB for the Sapta Marga Road Drainage building, Pematang Kandis Village, Bangko District, Merangin Regency, the total value is Rp. Rp.274,700,000.00 (Two Hundred Seventy Four Million Seven Hundred Thousand Rupiah).